RECOVERY OF RESIDUAL CRUDE PALM OIL FROM PALM OIL MILL EFFLUENT THROUGH PROGRESSIVE FREEZING - MOHAMED ANUAR, MUHAMMAD ATHIR (2021)
Oil extraction rate (OER) is one of the critical factors in assessing the performance and efficiency of the palm oil mill. Under Palm Oil National Key Economic Area, Malaysia is expected to achieve OER value up to 23% in 2020. One of the approaches to achieve this goal is to study the potential of recovering the residual oil from palm oil mill effluent (POME). A new method called progressive freezing (PF) was introduced to recover the residual oil from POME where it forms a single solid oil in the system. The crucial elements to figure out the performance of PF is the solution’s movement. In this study, the recovery of the residual crude palm oil (CPO) from POME was conducted through a circulated freeze crystallizer (CFC), at which the solid oil formed on the top and the side wall of the crystallizer. The PF’s performance via the CFC was compared with the performance obtained in a stirred tank crystallizer (STC) applied in a previous study. The results show that CFC is more effective than STC since it can recover the residual oil up to 88.65±3.0%. The system efficiency is also portrayed by the sample’s final oil and grease content of 44.83±3.0 and pH value of 6.1±1. In the subsequent performance analysis, an optimization technique called response surface methodology (RSM) with the design of rotatable central composite design (RCCD) was applied to investigate the interactive effects among the independent variables and to figure out the optimum experimental variables generated by Design-Expert software (version 6.0.4. Stat-Ease, trial version). The physicochemical characterization was also analysed to determine the quality of recovered oil. From the results, the PF process through the CFC has successfully recovered residual oil from the POME samples. The optimum process condition that yielded the best oil recovery percentage (Y) was the coolant temperature of 6 ⁰C, freezing time 50 minutes, and circulation flowrate of 500 rpm. The residual oil exhibit free fatty acid (FFA) content of 25 to 27%, deterioration of bleachability (DOBI) between 2.3 to 2.7, moisture content between 1.01 to 2.02% and dirt from 0.049 to 0.055. It can be concluded that the recovered oil can be recycled or utilized as value-added product such as biodiesel production.